Creating the theory of virtual learning environments : an example of a language forum - Rakhmankulova, Elena (2010)
Nowadays, the potential of virtual environments in education is widely acknowledged. With the paradigm shift of learning and teaching from behaviourism and cognitivism to constructivism, computer-assisted language learning (CALL) and virtual learning environments (VLE) in particular appeared to be perfect tools for putting the main ideas of the new approach into practice. The new technology is currently used in teaching various subjects such as medical education, mathematics, physics, chemistry, and language learning to name just a few, and its popularity is increasing. Nevertheless, there have been no attempts made to study the phenomenon of VLE as such. Current research investigates the theoretical background of a VLE, in general, and the characteristics that make or do not make a language forum a VLE, in particular. There has been extensive theoretical and experimental research on the use and advantages of VLEs. However, a coherent theory of VLEs is lacking and many experiments are done without grounding the assumptions in the theory. To build the theory of VLEs, this research sets the crucial definitions of virtual reality (VR), virtual environment (VE) and VLE, discusses the ground for the use of VLEs in education and characteristics of modern VLEs, compares different kinds of VLEs (2D, 3D and 2D+3D) and identifies their common characteristics. The set of defined characteristics is used in this research to analyze if a forum, a 2D or text-based VLE, can be an independent VLE metaphor and explains the reasons for such conclusion. This research is conducted qualitatively in the framework of grounded theory. Data from previous research on VLEs and second language learning and second language acquisition theory (SLL/SLA), available information about virtual environments and worlds, and observation of the area, i.e. the forum are analyzed to build a description of VLEs. Initially, the VLE characteristics are conceptualized on the basis of the theoretical data to be tested in the analysis of a language learning forum. The research result is a set of characteristics of VLE to serve as a basis for further experimental research. The factors of constructivist VLEs are a representation of the real world, knowledge construction, authenticity, case-based orientation, reflection, and collaboration and negotiation of meaning. They are found in other learning environments as well. The factors specific to VLEs are a construction of an environment and its objects, social structure and sense of presence or immersion. All of the characteristics are found in the language learning forum. This is the criterion to define a forum as a VLE; otherwise a forum as such is not necessarily a VLE. The research also reveals that existing studies on immersion do not adequately allow measuring its level and this question requires further independent research. Therefore, current research accepts that there is a sense of presence on the forum, but it questions the existence of immersion and its kinds.